THE USE OF PARALINGUISTICS IN JIM BUTCHER'S WORK - Masharipova, Valentina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
In this article, we explore the use of paralinguistics in Jim Butcher's work, specifically in his popular series, The Dresden Files. Through a comprehensive analysis of various paralinguistic cues used in his writing, we delve into how Butcher creates a rich and immersive reading experience for his fans.